2022
DOI: 10.7759/cureus.29309
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Pseudomyxoma Peritonei Arising From Primary Mucinous Ovarian Neoplasms

Abstract: Pseudomyxoma peritonei (PMP) is a rare manifestation of primary mucinous neoplasms. We report two rare cases of PMP originating from mucinous primary ovarian neoplasms. The case series discusses the cases of female patients aged 86 and 52 years who presented with worsening dyspepsia, abdominal distension, pelvic pain, and altered bowel habits. Both of the patients underwent evaluation comprising cancer antigen-125 (CA-125) levels, ultrasound (US) examination of the abdomen and the pelvis, tumor markers, cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Our patient's presentation primarily involved a two-year history of abdominal distension and vague abdominal pain. This feature aligns with the case reported by Joseph et al, which described worsening indigestion and abdominal distension within a two- to three-month timeframe [ 8 ]. In contrast, the case reported by Sarpietro et al presented with infertility and pelvic pain, while Pantiora et al described a patient with changing bowel habits over a year [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our patient's presentation primarily involved a two-year history of abdominal distension and vague abdominal pain. This feature aligns with the case reported by Joseph et al, which described worsening indigestion and abdominal distension within a two- to three-month timeframe [ 8 ]. In contrast, the case reported by Sarpietro et al presented with infertility and pelvic pain, while Pantiora et al described a patient with changing bowel habits over a year [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with the cases by Pantiora et al, both males in their late 50s [7]. However, our case diverges from Joseph et al who reported an 86-year-old female patient with PMP [8], and Sarpietro et al who described a 37-year-old female diagnosis [9]. These age discrepancies highlight the variable presentation of PMP, extending beyond middle age, as seen in Joseph et al's [8] study, and encompassing younger individuals, as noted by Sarpietro et al [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation